Respuesta :

Answer: x=6

Step-by-step explanation:

Step 1: Remove parentheses.

4(2x-5)-6=6+9+2x-54(2x−5)−6=6+9+2x−5

Step 2: Simplify  6+9+2x-56+9+2x−5  to  2x+102x+10.

4(2x-5)-6=2x+104(2x−5)−6=2x+10

Step 3: Expand.

8x-20-6=2x+108x−20−6=2x+10

Step 4: Simplify  8x-20-68x−20−6  to  8x-268x−26.

8x-26=2x+108x−26=2x+10

Step 5: Add 26 to both sides.

8x=2x+10+268x=2x+10+26

Step 6: Simplify  2x+10+262x+10+26  to  2x+362x+36.

8x=2x+368x=2x+36

Step 7: Subtract 2x2x from both sides.

8x-2x=368x−2x=36

Step 8: Simplify  8x-2x8x−2x  to  6x.

6x=36

Step 9: Divide both sides by 6.

x= 36/6 as a fraction

Step 10: Simplify  \frac{36}{6} to 6.

x= 6x